Urdu as Soft Power: Language, Diaspora, and India’s Cultural Diplomacy in the Gulf States - Mohammad Shahnawaz (Journal of Asian Social Science Research, 2026)
Abstract Large-scale South Asian migration to the Gulf since the 1970s has created enduring linguistic and cultural connections between India and the Gulf Cooperation Council states. Despite the substantial Indian diaspora in the region, research on India’s diaspora diplomacy has concentrated mainly on labour, remittances, trade, and strategic relations, leaving Urdu’s role in cultural influence insufficiently examined. This article investigates how Urdu functions as a soft-power resource in the Gulf and assesses its place within India’s official cultural diplomacy. Using a qualitative multi-method design based on secondary sources, it analyses peer-reviewed scholarship, policy documents, institutional reports, Urdu literary materials, news coverage, organisational records, and digital archives. The findings show that Urdu operates as a heritage language, lingua franca, medium of cultural memory, and platform for transnational interaction through literary events, organisations, cinema, music, education, journalism, and digital media. However, these activities are sustained largely by expatriate civil society and remain weakly incorporated into state policy. The article contributes to soft-power scholarship by conceptualising Urdu as relational linguistic soft power produced through diaspora networks. It concludes that stronger institutional partnerships with Urdu organisations could enhance cultural diplomacy, provided their autonomy and community-based character are preserved.